Explaining Away Incompatibilist Intuitions. (24th August 2012) - Murray, Dylan; Nahmias, Eddy
<x xml:space="preserve">Abstract</x> The debate between compatibilists and incompatibilists depends in large part on what ordinary people mean by 'free will', a matter on which previous experimental philosophy studies have yielded conflicting results. In Nahmias, Morris, Nadelhoffer, and Turner (2005, 2006), most participants judged that agents in deterministic scenarios could have free will and be morally responsible. Nichols and Knobe (2007), though, suggest that these apparent compatibilist responses are performance errors produced by using concrete scenarios, and that their abstract scenarios reveal the folk theory of free will for what it actually is—incompatibilist. Here, we argue that the results of two new studies suggest just the opposite. Most participants only give apparent incompatibilist judgments when they mistakenly interpret determinism to imply that agents' mental states are bypassed in the causal chains that lead to their behavior. Determinism does not entail bypassing, so these responses do not reflect genuine incompatibilist intuitions. When participants understand what determinism does mean, the vast majority take it to be compatible with free will. Further results indicate that most people's concepts of choice and the ability to do otherwise do not commit them to incompatibilism, either, putting pressure on incompatibilist arguments that rely on transfer principles, such as the Consequence Argument. We discuss the implications of these findings for philosophical debates about free will, and suggest that incompatibilism appears to be either false, or else a thesis about something other than what most people mean by 'free will'.